PD-L1+ neutrophils mediate immune regulation of CD8+ T cells in halo nevi - Zhang, Yixuan; Xu, Yingying; Cui, Wenjun; Wang, Haoyang; Li, Min; Liu, Lu (Frontiers in Immunology, 2025)
BackgroundHalo nevi are clinically common and are characterized by a circle of leukoderma around the central melanocytic nevus. Studies have shown that the pathogenesis of halo nevi is similar to that of vitiligo and is associated with the role of CD8⁺ T lymphocytes in melanocyte destruction. Histopathological findings have revealed neutrophil infiltration in halo nevi; however, the specific immune mechanisms involving neutrophils have not been thoroughly investigated. In the present study, we investigated the role of neutrophils in halo nevi using histopathological and immunological analyses.MethodsTo this end, we examined the infiltration patterns of immune cells in halo nevi, with a particular focus on IFN-γ-induced PD-L1 expression in neutrophils and its potential immunoregulatory effects.ResultsThe results demonstrated that IFN-γ expression in the lesional skin of halo nevi contributed to the induction of PD-L1 expression in neutrophils. PD-L1⁺ neutrophils promoted apoptosis and suppressed the function of CD8⁺ T lymphocytes. Notably, some halo nevi showed a tendency to spontaneous regression, but the underlying mechanisms remain unclear, and this regulatory mechanism influences the local immune response and may facilitate the repigmentation of the surrounding leukoderma in halo nevi.ConclusionsThis study is the first to explore the involvement of neutrophils in halo nevi and reveal the potential immunoregulatory role of PD-L1 in this process. The elucidation of this mechanism not only provides a more comprehensive understanding of autoimmune skin diseases but may also offer new strategies for targeted therapy in other related disorders, such as vitiligo.